2023
DOI: 10.5530/pj.2023.15.5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antidiarrheal, Antispasmodic, and Antisecretory Activities of Extract and Fractions of Castanopsis costata Leaves in Animal Models

Abstract: Several studies found that diarrhea damages the intestinal antioxidant defense system, culminating in further complications and other oxidative stress disorders. Therefore, antioxidants can play an important role in the management of diarrhea. [10][11] There are currently no detailed investigations on the antidiarrheal phytoconstituents of C. costata, but it is known to contain alkaloids, flavonoids, tannins, steroids, and others, which majorly have antidiarrheal activities. 8,12 Therefore, this study aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Leaf extract of this plant has been used empirically for the treatment of fever, digestive disorders, inflammation, wound healing, and pain relief ( 9 ). Meanwhile, several previous studies reported that C. costata leaf extract has pharmacological activity such as antimalarial ( 10 ), antidiabetic ( 11 ), anti-hypercholesterolemia ( 12 ), antioxidant ( 7 ), and antidiarrheal ( 13 ). Although there is an existing report on the traditional and scientific use of C. costata leaf extract, there are no reports in the literature on the anti-inflammatory, antipyretic, analgesic, and antioxidant activities of C. costata leaf fractions (CcLF).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf extract of this plant has been used empirically for the treatment of fever, digestive disorders, inflammation, wound healing, and pain relief ( 9 ). Meanwhile, several previous studies reported that C. costata leaf extract has pharmacological activity such as antimalarial ( 10 ), antidiabetic ( 11 ), anti-hypercholesterolemia ( 12 ), antioxidant ( 7 ), and antidiarrheal ( 13 ). Although there is an existing report on the traditional and scientific use of C. costata leaf extract, there are no reports in the literature on the anti-inflammatory, antipyretic, analgesic, and antioxidant activities of C. costata leaf fractions (CcLF).…”
Section: Introductionmentioning
confidence: 99%